Effect of 410 nm Diode Laser Irradiation on Human Sperm Motility in Vitro - Sama E. Mohammed; Layla M.H. Al-ameri (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Infertility can be defined asan absence of pregnancy after 12 months of regular unprotectedsexual intercourse,the most important of the sperm function disorders are reduced sperm motility(asthenospermia). Photobiomodulation have an effect on the decrease of the sperm disorder. Materialsand Methods: Diode laser with wavelength of 410nm was used to induce the sperm motility in anasthenozoospermia human seminal fluid in vitro,20 fresh seminal fluids samples were used in this study andeach sample was divided into two parts, one of them non-irradiated by laser light (control) and the other wasexposed to laser irradiation with exposure time of 30 secondsof 410nm diode laser with 0.67 W/cm2, powerdensity. Results: Progressive motility was significantly increase while non- progressive motility was nonsignificantly increased and the immotile spermswere significantly decreased at 5 min following irradiationcompared to non-irradiated samples,while at 15,30,45 minfollowing irradiation begin to decreased. Wefound that low power laser could induce a short term bio stimulation effect on sperm motility